2001
DOI: 10.1292/jvms.63.505
|View full text |Cite
|
Sign up to set email alerts
|

Glycoconjugate in Rat Taste Buds.

Abstract: ABSTRACT. The taste buds of the fungiform papillae, circumvallate papilla, foliate papillae, soft palate and epiglottis of the rat oral cavity were examined by lectin histochemistry to elucidate the relationships between expression of glycoconjugates and innervation. Seven out of 21 lectins showed moderate to intense staining in at least more than one taste bud. They were succinylated wheat germ agglutinin (s-WGA), Dolichos biflorus agglutinin (DBA), Bandeiraea simplicifolia lectin-I (BSL-I), Ricinus communis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
4
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
3
4
0
2
Order By: Relevance
“…Since beta-N-acetylglucosamine is ubiquitously localized in all types of papillae in all mammals examined, it might play an essential role in the taste bud function. As for alpha-fucose, the present results positively correlated with the previous reports on the localizations of glycoconjugates in the rat [4], rabbit, frog and fish [3,4,[14][15][16][17][18]. In contrast, certain glycoconjugates were unique in some but not all types of papillae, such as alpha-N-acetylgalactosamine, alpha-mannose and alpha-D-glucose.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Since beta-N-acetylglucosamine is ubiquitously localized in all types of papillae in all mammals examined, it might play an essential role in the taste bud function. As for alpha-fucose, the present results positively correlated with the previous reports on the localizations of glycoconjugates in the rat [4], rabbit, frog and fish [3,4,[14][15][16][17][18]. In contrast, certain glycoconjugates were unique in some but not all types of papillae, such as alpha-N-acetylgalactosamine, alpha-mannose and alpha-D-glucose.…”
Section: Discussionsupporting
confidence: 91%
“…WGA, s-WGA, LEL and STL bind to beta-N-acetylglucosamine), the binding patters of these lectins differed greatly among animals and/or taste papillae. As it has been postulated that lectins identify three-dimensional structures of glycoconjugates [4], the present results suggest the differences in the spatial molecular structures of glycoconjugates that even when cells in the taste buds show the same distribution patterns of lectin bindings. Specific bindings to certain types of cells have been reported in the tongue [11,13]; for example, Taniguchi, et al (2005) reported that PNA bound to type IV cells of the rat taste buds [13].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Багато дослідників вивчали експресію глікоко-н'югатів у клітинах смакових бруньок різних тварин з використанням методів лектинової гістохімії, як корисного інструменту для визначення вуглевод-них детермінант клітинної поверхні. Лектини вико-ристовуються для ідентифікації конкретних популя-цій клітин на основі різної спорідненості з різними вуглеводними епітопами поверхні клітинної мемб-рани, а також дозволяють вивчати динаміку пере-розподілу глікокон'югатів у складі клітин та екстра-целюлярних структур як у фізіологічних умовах, так і при патології [11][12][13][14][15].Мета дослідження. З використанням методів лектинової гістохімії дослідити вплив натрієвої солі глутамінової кислоти на вуглеводні детермінанти структурних компонентів жолобуватого сосочка язика.…”
unclassified